2008
DOI: 10.2172/1130404
|View full text |Cite
|
Sign up to set email alerts
|

ASEDRA Evaluation Final Report.

Abstract: Transforming Urgent and Emergency Care and the Vanguard Initiative For more information on this publication, visit www.rand.org/t/RR2062 Published by the RAND Corporation, Santa Monica, Calif., and Cambridge, UK © Copyright 2017 RAND Corporation R® is a registered trademark. RAND Europe is a not-for-profit organisation whose mission is to help improve policy and decisionmaking through research and analysis. RAND's publications do not necessarily reflect the opinions of its research clients and sponsors. Limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(20 citation statements)
references
References 4 publications
0
20
0
Order By: Relevance
“…27 For example, the 2018 evaluation of the TIS program suggested it is meeting its short-term goals (including growth in partnerships and community engagement, increased access to culturally appropriate quitting support, and an increase in the use of evidence to inform program design), but the long term impact in relation to a reduction of smoking rates was said to be outside the scope of the evaluation. 10 A more recent national 2018-2020 study used a cohort design to examine smoking-related attitudes and behaviours among Aboriginal and Torres Strait Islander adults. 3 The Mayi Kuwayu Study found no differences in overall smoking prevalence, but some significant differences in smoking behaviours (such as a lower prevalence of smoking inside the home) among respondents living in TIS funded areas, compared to non-TIS funded areas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…27 For example, the 2018 evaluation of the TIS program suggested it is meeting its short-term goals (including growth in partnerships and community engagement, increased access to culturally appropriate quitting support, and an increase in the use of evidence to inform program design), but the long term impact in relation to a reduction of smoking rates was said to be outside the scope of the evaluation. 10 A more recent national 2018-2020 study used a cohort design to examine smoking-related attitudes and behaviours among Aboriginal and Torres Strait Islander adults. 3 The Mayi Kuwayu Study found no differences in overall smoking prevalence, but some significant differences in smoking behaviours (such as a lower prevalence of smoking inside the home) among respondents living in TIS funded areas, compared to non-TIS funded areas.…”
Section: Discussionmentioning
confidence: 99%
“…10 The program was revised and replaced in 2015 with the Tackling Indigenous Smoking (TIS) program, which includes grant funding for regional tobacco control activities, a range of national supports for implementation, performance monitoring and evaluation and enhanced Quitlines. 10 The TIS program was evaluated in 2018, with results suggesting it would contribute to a reduction in smoking rates. 3,11 Informed consent was implied by completion of the online survey.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They're going to come on. We get them at 12, 13, 18, 20 years of age… (Mitchell, 2008) Presenters do not experience their audience as a discrete object. Instead they know their audience collectively as a relational subject.…”
Section: Institutional Solutions: the 'By-the-book Audience'mentioning
confidence: 99%
“…The second goal is to estimate the amount of each isotope thought to be present in the item. One key validation step in any modern RIID is to simulate data assuming that the item contains the chosen isotope subset using a "forward model" that requires an estimate of the gamma detector response function (DRF) [11][12][13][18][19][20][21]. If the simulated data agree reasonably well with the observed data, then there is reasonable confidence that the inferred subset is at least close to correct.…”
Section: Introductionmentioning
confidence: 99%